Nexus of energy efficiency, carbon emission and economic growth in Nigeria - Danfoso Adama Tijani; Olure-Bank Adeyinka; Dennis Michael (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Given rising temperatures, climate change, the alarming increase in energy demand, and the importance of energy efficiency, there is a need for an increasing review subject matter. In this sense, policymakers develop various measures, including renewable adoption and energy efficiency. This study examined the causal effect of oil production and carbon emission from gas flaring on the economic growth rate in Nigeria from 1980-2021. The findings revealed that economic growth and energy consumption significantly increases energy-related emissions. An increase in income level influences investors and industrialists to invest in the industrial sector, increasing production, diversification, and expansion. However, increased production and expansion of industries increase energy demand. Energy demand met by consuming fossil fuel increases energy-related emissions in Nigeria and negatively affects environmental quality. More importantly, carbon emission impedes environmental sustainability and sustainable economic growth in Nigeria. The study is relevant to the post-2015 Sustainable Development Goals agendas for two fundamental reasons: the world needs Sustainable Development Goal 7 – ensuring access to affordable, reliable, sustainable, and modern energy by 2030. (b) Large extractive industries primarily drive growth in Nigeria, and the country's population is expected to double in about 30 years. Energy efficiency for inclusive development is very welcome. This is essential because studies have shown that the increase in unemployment (resulting from the underlying demographic change) would be accommodated by only the private sector, not the public sector.